2019
DOI: 10.1002/hon.2696
|View full text |Cite
|
Sign up to set email alerts
|

Simple acute phase protein score to predict long‐term survival in patients with acute myeloid leukemia

Abstract: High levels of acute phase reactants can be associated with adverse outcome in patients with various solid tumor types. For patients with acute myeloid leukemia (AML), this correlation is unknown. We retrospectively investigated the prognostic value of pretreatment acute phase protein levels in 282 consecutive newly diagnosed AML patients undergoing at least one cycle of intensive induction chemotherapy. We applied a new score integrating pre-treatment C-reactive protein (CRP), fibrinogen, and albumin levels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(47 reference statements)
0
8
0
Order By: Relevance
“… 17 Similarly, the Glasgow prognostic score (GPS) and modified GPS (mGPS), determined by the serum CRP and albumin levels, have been proposed as prognostic indicators for AML patients. 18 However, the clinical correlations of CAR and its prognostic value in AML patients have not yet been clarified. Therefore, we retrospectively investigated whether CAR has prognostic potential in patients with newly diagnosed non-M3 AML.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Similarly, the Glasgow prognostic score (GPS) and modified GPS (mGPS), determined by the serum CRP and albumin levels, have been proposed as prognostic indicators for AML patients. 18 However, the clinical correlations of CAR and its prognostic value in AML patients have not yet been clarified. Therefore, we retrospectively investigated whether CAR has prognostic potential in patients with newly diagnosed non-M3 AML.…”
Section: Introductionmentioning
confidence: 99%
“…AML, like many other malignancies, is an inflammatory disease and there are ongoing attempts to incorporate acute phase proteins such as albumin into predictive models 22,[27][28][29]. Heini et al, conducted a retrospective evaluation of the prognostic value of Creactive protein, fibrinogen and albumin (CFA) levels in a ratio and found that patients with a lower CFA ratio had longer progression free survival, disease free survival and OS (61.2 vs. 13.8 months, p < 0.01) after intensive treatment relative to those with a higher CFA ratio 29. Similarly, a novel predictive model for OS was created by Silveria et al in newly diagnosed AML combining an adaptive genetic risk score and clinical prognostic parameters including hypoalbuminemia (defined as <3.8 g/dl) 30.…”
mentioning
confidence: 99%
“…It is assumed that 75%-85% (9-14 μmol/L) of Zn in the body is bound to albumin, which is the major part of the Zn exchange pool. In this study, SCZR was closely related to ALB and CRP levels, which were reported to be associated with adverse outcomes in patients with newly diagnosed AML undergoing intensive induction [40,41]. Previous studies revealed the validity of the SCZR for the severity of nutritional status, inflammation, oxidative stress, immune dysfunction, and infection associated with Zn deficiency [42].…”
Section: Discussionmentioning
confidence: 62%